RESEARCH OF VARIOUS ISO-MANIFOLDS IN FOUR COMPONENT SYSTEMS CONTAINING BIAZEOTROPIC BINARY CONSTITUENTS - F. N. Bedretdinov; T. V. Chelyuskina (Тонкие химические технологии)
In the present work, an analysis of the mutual arrangement of a number of iso-manifolds in the concentration tetrahedron formed by the components of the separated mixture and an additional substance, an extractive agent, was carried out to estimate the possibility of separating three-component mixtures containing biazeotropic constituents by extractive rectification. The objects of research were four-component systems formed by ternary constituents (butyl propionate (BP) - propionic acid (PA) - butyl butyrate (BB), butyl propionate - propionic acid - butyric acid (BA), butyl butyrate - butyric acid -butyl propionate, butyl butyrate - butyric acid -propionic acid) of the commercially important BP-PA-BB-BA system, and the extractive agent sulfolane. Using the results of the computational experiment based on mathematical model NRTL-HOC we obtained complete data on the vapor-liquid equilibrium in binary, three- and four-component systems. The structures of liquid-vapor phase diagrams were obtained, and thermodynamic-topological analysis of all four-component systems was carried out. The mutual arrangement in the concentration tetrahedron of manifolds of relative volatility (equal to 1) of the components, reflecting the evolution of pseudo-azeotropes in sections with a constant concentration of the extractive agent; pseudo-ideal manifolds along which the activity coefficients of the components of the base (separated) mixture are equal to each other; isothermo-isobaric manifolds generated by Bancroft points in binary azeotropic constituents were determined. We established that it is possible to separate the studied three-component mixtures by extractive rectification using sulfolane.